SOCIO-ECONOMIC CHANGES IN POLAND - A CHALLENGE TO THE EDUCATIONAL SYSTEM. SELECTED ASPECTS OF SOCIOLOGY (Pedagogy of Higher and Secondary Education, 2004)
The author investigates the problem of the influence of social and economic changes on the system of education in the country.